Power saving techniques in access networks - Hajduczenia, Wojciech (2013)
Our modern society interacts with the surrounding through various electronic devices, causing ever growing demand for energy around the world. Energy usage of Information and Communication Technology (ICT) devices in Portugal (based on reports of Portugal Telecom) are examined in this thesis, along with current trends around the world. Various characteristics (components, protocols, software and traffic periodicity) of known access technologies, including wireless, wired optical and copper media, were examined in detail while performing the study of energy consumption in the access networks. Detailed analysis of power saving methods meeting the contracted Service Level Agreements (SLAs) was also carried out. Ways to save power were classified into active (requiring adaptation to the load conditions with the use of algorithms and software), passive (more efficient components) and hybrid (combination of active and passive methods). To study the potential for power saving in various access network architectures, a data trace analysis software was developed in Matlab environment. This program examines user activity profiles based on real data traces, performing necessary aggregation for selected activity profiles, and calculates overall power consumption and power saving potential while taking device characteristics into consideration. Conclusions on the power saving capacity of various access technologies are drawn based on the developed software model. Possible future research topics, including development of a global database with detailed information about power consumption in network devices, studying the effects of various combinations of power saving mechanisms on network performance, were also listed in Chapter 5, “Future studies”. Annex A contains a brief overview of access technologies. Annex B provides a detailed tutorial with examples for the designed data analysis software, providing a starting point for any future user of this software model.